The Effect of Multi-Type Learning Media on Students' Learning Outcomes in Islamic Religious Education at Junior High School - Humairoh Firdaus; Siti Nursyamsiyah; Badrut Tamami (JGK (Jurnal Guru Kita), 2026)
Islamic Religious Education (IRE) learning at Muhammadiyah 4 Junior High School in Purwoharjo continues to rely largely on conventional teaching methods, which may reduce student engagement and limit learning outcomes. This study aimed to examine the effect of learning media utilization on students’ learning outcomes in Islamic Religious Education. A quantitative research design was employed using a total sampling technique involving all 95 students of the school. Data were collected through structured questionnaires and observations and analyzed using simple linear regression. The results revealed that learning media utilization had a positive and statistically significant effect on students’ learning outcomes, as indicated by the regression equation Y = 3.537 + 0.631X and an R-square value of 0.823. These findings demonstrate that learning media account for 82.3% of the variance in students’ learning outcomes, indicating a substantial contribution to academic achievement. The study suggests that the integration of diverse learning media can enhance student engagement, improve understanding of learning materials, and support better learning outcomes in Islamic Religious Education at the junior high school level.